Pemanfaatan Aplikasi Canva sebagai Media Pembelajaran Membaca dan Berhitung Bernuansa Banjar untuk Siswa Sekolah Dasar - Arnida, Tika; Lisnadia, Lisnadia; Nurra, Siti; Yolanda, Yolanda; Dila, Ratna; Nurmeidina, Rahmatya (Abdimas Universal, 2025)
Instructional media encompasses all resources that can be utilized to systematically convey content from educators to students, thereby facilitating effective and efficient learning. The objective of this community service initiative is to provide educational media for reading and arithmetic, including cards, posters, and videos, by leveraging the Canva application. The method employed in the execution of this initiative involves mentoring during the learning process and training in the use of the Canva application. Data collection techniques include a pre-test to assess students' initial reading and arithmetic abilities, followed by a post-test to evaluate any subsequent improvements in these skills. The results indicate a significant enhancement in students' reading abilities, with an increase of 28 points, and a 23-point improvement in arithmetic skills. Additionally, this activity has enabled teachers to become more acquainted with the Canva application, which has proven to be beneficial in the creation and development of instructional media.